KENDALI TEKTONIK TERHADAP PERKEMBANGAN CEKUNGAN EKONOMI TERSIER OMBILIN, SUMATRA BARAT (TECTONIC CONTROL ON THE DEVELOPMENT OF THE OMBILIN TERTIARY ECONOMIC BASIN, WEST SUMATRA) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT The Ombilin Basin is the Tertiary intermontane basin located in the Barisan Mountains, West Sumatra, and as a pull apart basin due to dextral movement of Silungkang Fault and Takung Fault since Paleocene. The basin has northwest:southeast direction, 60 km long and 30 km wide approximately, which is devided into two subbaSins by Tanjungampalu Fault and Bukit Tungkar Highland, they are Talawi Subbasin and Sinamar Subbasin. Tectonic evolution of Ombilin Basin can be studied from remote sensing and geological structure analysis (microtectonic analysis i.e. dihedral method and inversion method). Remote sensing analysis of the studied area on Landsat image path/row 127/060 revealed that Ombilin Basin development was controlled by Silungkang and Takung Faults as a pull apart basin, and consists of two successive subbasins